Patient Demographics Associated with Latissimus Dorsi Muscle Dimension for Flap Coverage Planning - Jacobi, Sophia; Sadeh, Omer; Davidovic-Katz, Emily; Moll, Samara; Barrera, Janos A; Hacquebord, Jacques Henri (Journal of Reconstructive Microsurgery)
Background: The latissimus dorsi (LD) is a common workhorse flap used in reconstructive surgery to cover large wound defects. Estimating the area of possible coverage is necessary for preoperative planning and surgical success. The aim of this study is to investigate the relationship between patient factors and the measurable dimensions of the LD flap in order to inform more personalized preoperative planning and evidence based flap selection. Methods: This is a retrospective study of individuals who underwent computed tomography (CT) angiography of the chest and abdomen. Patient demographics – height, age, sex, and body mass index (BMI) were collected. The primary outcome was the dimensions of the LD muscle edges and length of the thoracodorsal pedicle measured on CT. Multivariable linear regression was performed to determine the independent effects of patient demographics on the dimensions of the latissimus dorsi muscle. Results: A total of 50 patients were included in this study. Patient demographics were significantly associated with all LD muscle dimensions. The length of the vascular pedicle was 9.502 土 1.281 cm and was significantly associated with height (p<0.001). Patient demographics had a strong correlation (r=0.957) with this length. The average wound defect area the latissimus dorsi can cover was 209.99 cm2 (range: 114.24 cm2 to 312.40 cm2). This area increases or decreases by 1.498 cm2 per centimeter change in a patient’s height (p=0.011). Conclusion: An understanding of how patient factors are associated with LD muscle dimensions is critical for preoperative planning and surgical success. Our study found that height, BMI, age, and sex all have associations with the dimensions of the latissimus dorsi muscle. As well, height is strongly correlated with the length of the thoracodorsal vascular pedicle, influencing the possible rotation arc of the flap.